Effectiveness of Traditional Chinese Medicine in Psychological Rehabilitation After Lung Cancer Surgery: Systematic Review and Meta-Analysis protocol - Luchang Cao PhD; Zilin Wang MM; Xinmiao Wang PhD; Guanghui Zhu PhD; Ying Zhang PhD; Jie Li PhD (Integrative Cancer Therapies)
Background: The incidence and mortality of lung cancer is the highest among malignant tumors worldwide, and it seriously threatens human life and health. Surgery is the primary radical treatment for lung cancer. However, patients often experience discomfort, changes in social roles, economic pressures, and other postsurgical challenges. These factors frequently cause various psychological disorders such as anxiety and depression, significantly diminishing the quality of life and elevating the risks of recurrence, metastasis, and mortality. Therefore, effective strategies for mental function rehabilitation should be urgently developed. Traditional Chinese medicine can significantly improve psychological function and physical symptoms after lung cancer surgery, and prolong patient survival. However, its effectiveness for mental function rehabilitation after lung cancer surgery remains unclear. This study aimed to investigate the effects of Chinese medicine on mental function recovery after lung cancer surgery through a systematic review and meta-analysis. Methods: This study will systematically search the following databases: PubMed, Cochrane Library, EMBASE, Web of Science, ClinicalTrials.gov, China National Knowledge Infrastructure, Wanfang database, VIP database, and Chinese BioMedical Literature database. Search for studies published from the inception of each database until April 22, 2024. This study will be limited to clinical randomized controlled trials (RCTs). The primary outcome will be depression or anxiety, as indicated by the scale score. Data analysis will be performed using RevMan 5. The Cochrane Risk of Bias Assessment Tool will be used to evaluate the quality of included studies. Finally, the quality of the evidence will be classified using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) System. Results: This meta-analysis aims to offer comprehensive evidence of the effectiveness of traditional Chinese medicine in mental function rehabilitation after lung cancer surgery. The study will assess the quality of the reports and conduct a subgroup analysis based on various postoperative stages, intervention measures, intervention duration, and sex to gather more evidence to fill the gap in psychological function rehabilitation after lung cancer surgery. These data can be used to guide clinical practice and inform future studies. More importantly, the results of this study will provide evidence to support the development of expert consensus and clinical guidelines in the field of mental function rehabilitation after lung cancer surgery.